1987
DOI: 10.1111/j.1365-2621.1987.tb05894.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Green Beans, Bell Peppers and Spinach Stored in Polyethylene Bags

Abstract: Quality attributes of packaged and unpackaged vegetables generally decreased nonlinearly during storage at 10°C or ZO"C, and most of the decrease was greater at 20°C than at 10°C. Packaging reduced weight loss of green beans and spinach kept at 20°C; and reduced chlorophyll loss of green beans at 10°C and of spinach at 20°C. Ascorbic acid (vitamin C) benefited by packaging of green beans and spinach kept at 10°C. Packaging had an effect on thiamin (vitamin Br) of only spinach held at 10°C and 20°C and had no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
1
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 5 publications
5
18
1
1
Order By: Relevance
“…Serrano et al [142] stored broccolis using macroperforated, microperforated and non-perforated polypropylene films and observed that all changes related to loss of quality were significantly reduced and delayed with time especially with perforated and non-perforated films. Packaging of pepper with plastic films extend the shelf life but the major benefit appears to be mediated by the maintenance of high relative humidity inside the package which reduces the rates of transpiration [21,70,108,161].…”
Section: Current Application Of Polymeric Films For Map Of Fruits Andmentioning
confidence: 99%
“…Serrano et al [142] stored broccolis using macroperforated, microperforated and non-perforated polypropylene films and observed that all changes related to loss of quality were significantly reduced and delayed with time especially with perforated and non-perforated films. Packaging of pepper with plastic films extend the shelf life but the major benefit appears to be mediated by the maintenance of high relative humidity inside the package which reduces the rates of transpiration [21,70,108,161].…”
Section: Current Application Of Polymeric Films For Map Of Fruits Andmentioning
confidence: 99%
“…(1), was assumed for predicting individual Y k response variables (Watada et al, 1987;Montgomery, 1991 where bk o , bk i , bk ii , and bk ij are regression coefficients and X i the coded independent variables, linearly related to c C , c A , and t ( Table 1). The factorial design described was used for samples packaged in mono-oriented polypropylene bags (OPP) and in low density polyethylene bags (LDPE) (29 runs for each type of packaging film).…”
Section: Experimental Designmentioning
confidence: 99%
“…Previous research has focused on the packaging of bell peppers (Ben-Yehoshua et al 1983;Brackett 1990;Bussel and Kenigsberger 1975;Lurie et al 1986;Miller et al 1986;Watada et al 1987). Many of these studies examined the use of individual film-wrapping (shrink wrap).…”
Section: Introductionmentioning
confidence: 97%